OsGATA7 and SMOS1 cooperatively determine rice taste quality by repressing OsGluA2 expression and protein biosynthesis - Ni Cao; Wei Zhou; Fengli Zhao; Guiai Jiao; Lihong Xie; Ao Lu; Jiamin Wu; Maodi Zhu; Yongqiang Liu; Junming Yu; Rumeng Zhao; Xinyi Yang; et al. (Nature Communications)
Abstract Taste is crucial for the economic value of rice (Oryza sativa L.) and determines consumer preference. However, the mechanisms underlying taste formation have remained unclear. Here, we show that OsGATA7 contributes to desirable taste quality by affecting the swelling properties, texture, and taste value of cooked rice. OsGATA7 binds to the promoter of SMOS1, and activates its expression, thereby regulating taste quality. Furthermore, SMOS1 binds to the promoter of the protein biosynthesis gene OsGluA2, and recruits the PRC2 complex to repress its expression, leading to increased protein content. The overexpression of both OsGATA7 and SMOS1 reduces protein content and enhances taste quality. The haplotypes OsGATA7 Hap1 and SMOS1 Hap1 maintain low protein content and improve taste scores. Collectively, these findings reveal a regulatory mechanism for taste quality formation mediated by the OsGATA7–SMOS1 protein content module, and identify the elite haplotypes OsGATA7 Hap1 and SMOS1 Hap1 as a means to improve taste quality.